Design and Psychometric Testing of the Nurse Manager Span of Control Assessment Index - Ellen Swartwout; Brandy Mathews; Karen Drenkard (Journal of Nursing Measurement, 2026)
Background and Purpose: Adequate frontline nurse managers’ span of control (SOC) is critical for organizational success. This study evaluated the psychometric properties of the Nurse Manager SOC Assessment Index. Methods: Phase 1 included development of the instrument, item-level content validity index, expert review, and pilot and cognitive testing of the items. Phase 2 included psychometric testing using coefficient alpha to evaluate reliability, exploratory factor analysis, and principal component analysis to determine the underlying factors to explain SOC. Results: The final scale of nine items had a three-factor solution with 55.7% of the variance explained and coefficient alpha = .669 ( n = 265). Conclusions: The instrument is valid and reliable. Being exploratory in nature for the first iteration of the instrument, the reliability threshold for coefficient alpha was adequate; however, it was on the lower end of the threshold, supporting consideration for potential revisions and further testing of the instrument. The tool can be used to measure nurse manager’s SOC adequacy and adjust accordingly to impact nurse, patient, and organizational outcomes.